Alexithymia Is Related to the Need for More Emotional Intensity to Identify Static Fearful Facial Expressions - Starita, Francesca; Borhani, Khatereh; Bertini, Caterina; Scarpazza, Cristina (Frontiers in Psychology, 2018)
Individual differences in emotion processing, i.e. aIndividuals with high levels of alexithymia, a personality trait marked by difficulties in identifying and describing feelings and an externally oriented style of thinking, have been associatedappear to the need forrequire more time to accurately recognize intense static emotional facial expressions (EFEs). However, in everyday life, EFEs are dynamic and displayed at different levels of intensity and individuals with high alexithymia may also need more emotional intensity to identify EFEs. Nevertheless, which raises the question of the impactnfluence of alexithymia on the identification of these stimuliEFEs, which vary in emotional intensity, has largely been neglected. To address this, two experiments were conducted in which participants with low (LA) and high (HA) levels of alexithymia were assessed in their ability to identify static (Experiment 1) and dynamic (Experiment 2) morphed faces ranging from neutral to intense EFEs. Results showed that HA needed more emotional intensity than LA in identifyingto identify static fearful – but not happy or disgusted – faces. EFEs. On the contrary, no evidence was found that alexithymia affecteddid not impact the identification of dynamic EFEs. These results extend current literature suggesting that alexithymia is related to the need for more perceptual information to identify static but not dynamic fearful EFEs.